Language education as a site for identity negotiation: The practice of new immigrant language instruction in Taiwan - Haruna Kasai; Tzu-Bin Lin (Cogent Education, 2023)
AbstractSince the early 2000s, the Taiwanese government has been increasingly employing multiculturalism as a frame for imagining Taiwanese nationhood for political and economic strategy, aiming at strengthening ties with Southeast Asian countries. In recent years, the official imaginary of multicultural Taiwan has taken a new direction to include previously neglected groups of minorities, such as immigrants from Southeast Asian countries. In 2019, seven Southeast Asian languages were introduced into the national curriculum. While this reflects the government’s desire to include immigrants’ cultures and languages in the formal curriculum to promote a multicultural vision of Taiwanese identity, it also potentially creates a new avenue for immigrants to negotiate their identities in school classrooms. Through two case studies conducted at primary schools in New Taipei City, this study explores the interaction of local immigrant teachers and official identity discourses. Evaluating language education from a critical multicultural perspective, we argue that minority language instruction could be a catalyst for raising the status of the speakers of these languages in Taiwanese society, but only in so far as it signifies their genuine inclusion in the knowledge construction process.